Changes in properties of an alfisol produced by various crop covers - Lal, R.; Wilson, G.; Okigbo, B.N. (1979)
The effects of three grasses and five leguminous covers, grown on an eroded tropical Alfisol for two years, on soil properties were investigated. Improvements in soil characteristics under Brachiaria, Paspalum, Cynodon spp., Pueraria, Stylosanthes, Stizolobium, Psophocarpus, and Centrosema were compared with that of weed-fallow control. There were significant improvements in soil organic matter, total nitrogen, cation exchange capacity (CEC), infiltration rate, moisture retention at low suctions, and soil bulk density under various grass and leguminous fallow compared with control.